(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
Montenegro is a frontrunner in the EU accession process, and yet it is stagnating and even backsliding in terms of democracy and the rule of law. A question arising is whether the EU’s conditionality―under its new methodology, known as the “new approach”―regulating the EU accession process effectively strengthens democratic institutions there. This chapter argues that so far this approach has not worked successfully in Montenegro beyond the norm adoption phase for three main reasons: a lack of clarity about EU conditionality, the presence of long-ruling elites, and a specific national political culture. Through Europeanization theories, this research tests two areas in rule of law promotion: judiciary reform and freedom of the press. Based on a normative approach, the content of rules and laws in the judicial sector and freedom of expression are studied to challenge the EU’s external demands (rule adoption) empirically, by discussing the regular obstacles mentioned in the media and in reports by non-governmental organizations (implementation). In particular, the political and social context in which these dynamics operate is emphasized. Conclusions show that, while EU conditionality has brought an undeniably positive change in Montenegro and has successfully led to the adoption of new laws, implementing democratic institutions remains arduous since political elites overshadow integration. At the same time, checks and balances have eroded in the face of unpunished abuse of power. The study speaks to debates on Europeanization and ways to strengthen the rule of law along with EU standards in candidate member states and provides useful solutions to the failures of EU conditionality.